Pengelolaan Zakat Produktif (Burjo) Baznas Kota Cirebon di Tengah-tengah Kemiskinan Nelayan Kerang Hijau Samadikun - Ifah, Siti Latifah (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to examine the problem of poverty for Samadikun green mussel fishermen in an Islamic economic perspective, determine the implementation of productive zakat management in the Burjo program in the Samdik Community fishing community, and analyze the effectiveness of productive zakat management in the Burjo program in empowering Samdik Community green mussel fishermen. This study a qualitative research method with a phenomenological approach. The location of study is Samadikun alley X (Samdik Community) and the Cirebon city Baznas. The data meaning techniques used areobservation, in-depth interviews and documentation. The validity of the data is maintained through data, informant and time triangulation techniques are carried out until the are saturated. Furthermore, the data were analyzed using technical analysis by Miles and Huberman, through codification, reduction, elimination, and data display. The results of this study indicate that,based on an Islamic economic perspective, fishermen's poverty is caused by consumption and distribution activities in their economic system. Fishermen's consumption activities tend to deviate from the concept of consumption of dharuriyyah, tahsiniyatand hajjiyat needs. Meanwhile, structural poverty is caused by the existence of a capitalistic-style distribution system. This happens in the banking system that uses debt traps, in the distribution mechanism. This system is contrary to the concept of distribution in Islam which emphasizes the principles of freedom and justice. In such circumstances the Burjo program exists as a strategy in distributing assets to create economic justice. However, the implementation of the Burjo program on making cages was not matched by the creation of a distribution strategy by the fishing community. He is still trapped in the middleman-styledistribution system, so that Burjo's income only revolves around the seed capital. The remaining allocation of Burjo proceeds is directed at social service activities. Thus the Burjo program is less effective in efforts to increase and strengthen the economy to realize the welfare of fishermen.